Cell Sensitivity of Recultured Cellular SPEV Line and Candida albicans Fungi to Extra- and Intracellular Crystallisation Processes - Rozanov, L. F.; Vysekantsev, I. P.; Petrenko, T. F.; Kovalenko, I. F.; Koschij, S. V. (Problems of Cryobiology and Cryomedicine, 2004)
The freeze-thawing processes of SPEV cell suspensions and C. albicans fungi were investigated with a polarizing-interference microscopy. The SPEV cells were found out to be highly sensitive to an intracellular crystal formation, which depended in a considerable extent on the level of cell suspension supercooling prior to crystallisation beginning in an extracellular medium. C.albicans cells are more resistant to initiation of an intracellular crystal formation, that provides them a higher cryoresistance.